Cellular polyamines influence maturation and germination of somatic embryos from pro-embryonal masses of two grapevine cultivars - Nookapaju, A.; Barreto, M. S.; Agrawal, Dinesh C. (Vitis, 2008)
Somatic embryos of grapevine multiply repeatedly and often fail to mature and germinate due to factors like dormancy and embryo teratology. The present investigation was carried out to improve the maturation and germination of somatic embryos from pro-embryonal masses (PEM) of 2A-Clone and `Crimson Seedless', two seedless grapevine cultivars. Also, the aim was to study a correlation between cellular and residual polyamine (PA) levels in PEM and culture media. The efficiency of maturation and germination of embryos from PEM varied significantly between the two cultivars and depended on incubation period and type of PAs in the medium. HPLC analysis showed that higher levels of cellular putrescine in PEM had correlation with maturation and germination percentages in both cultivars. The levels of three PAs depleted in the media rapidly indicating its uptake by PEM. Of the three PAs, putrescine (PUT) was the most effective and resulted in 100.0 or 92.0 % maturation at 14 d or 30 d in 2A-Clone or `Crimson Seedless', respectively. The maximum germination of somatic embryos was recorded with PUT at 14 d or 21 d in 2A-Clone or `Crimson Seedless', respectively.
Keywords: germination; Grapevine; maturation; polyamines; `2A-Clone'; `Crimson Seedless'

High frequency occurrence of single cotyledonary embryo morphotype and repetitive somatic embryogenesis in `Thompson Seedless' crossed with seven grapevine male parents - Bharathy, P. V.; Agrawal, Dinesh C. (Vitis, 2008)
Direct somatic embryogenesis was observed in zygotic embryos rescued from intra- and inter-specific crosses between `Thompson Seedless' and seven male parents of grapevine when the embryos were cultured on Woody Plant Medium (WPM) supplemented with benzyladenine (1 mu M). Repetitive somatic embryogenesis occurred on the same medium, which also supported a high percentage of embryo maturation, germination and plantlet development. The cultures retained embryogenic potential for more than two years. We observed a high frequency occurrence of mono-cotyledonous embryo morphotype and other morphological variations in somatic embryos of all the crosses. The percentage of embryos having mono-, di-, tri-, multiple and abnormal cotyledons varied among the crosses. The overall percentage of monocot embryos was 35.50 %, as against 38.64 % of dicot embryos, while the germination rates for mono- and dicot- embryos were 24.44 % and 24.15 %, respectively. Shoot development was poor in tri- and multiple-cotyledonary embryos, while there was no shoot formation in abnormal embryos. We assume that the relatively high occurrence of single cotyledonary morphotype, may be due to the repetitive exposure of embryogenic tissues to a medium containing benzyladenine.
Keywords: cotyledon; Grapevine; somatic embryo; Vitis

Variability among vitis vinifera cultivars to in vitro propagation - Barreto, M. S.; Nookaraju, A.; Joglekar, A. M.; Karibasappa, G. S.; Agrawal, Dinesh C. (Proceedings of the International Symposium on Grape Production and Processing, 2008)
Response of grapevines to tissue culture has been reported to be genotype dependent, hence it becomes imperative to optimize culture conditions for newly developed varieties or cultivars, needing a large scale planting but availability of sufficient planting stock is a constraint. In the present study, conditions for in vitro propagation of six popular table grape cultivars have been standardized. Single node stem segments of cultivars 2A-Clone of Thompson Seedless, Red Globe, Crimson Seedless, Thompson Seedless, Flame Seedless and Italia cultured on ten different basal media showed varied percentages of bud break and morphogenetic responses. The percentage of bud break varied among the six cultivars. Direct rooting at basal ends of single node segments was observed in all the cultivars except in Italia. Woody plant medium induced the highest response and Eriksson medium the least in all the cultivars tested. Rooted nodal segments with shoots in axils could be established into whole plants on potting. Six cultivars showed different optimum concentrations of growth regulators for induction of maximum number of multiple shoots in both primary as well as secondary nodal segments. Shoot proliferation could be enhanced by several fold in the majority of cultivars on culture of initial shoot clumps to glass bottles instead of culture tubes. Six cultivars showed significant differences in optimum requirement of nutrients and growth regulators for shoot elongation, in vitro and ex vitro rooting and survival rate. Tissue culture plants of all the six cultivars could establish successfully in a greenhouse.
Keywords: basal media; Grapevine; growth regulators; micropropagation; Tissue culture; Vitis

Enhanced tolerance of transgenic grapevines expressing chitinase and beta-1,3-glucanase genes to downy mildew - Nookaraju, Akula; Agrawal, Dinesh C. (Plant Cell Tissue and Organ Culture, 2012)
An Agrobacterium-mediated transformation protocol for grapevine cv. Crimson Seedless using sonication and anti-necrotic agents has been optimized, and transgenic lines carrying wheat chitinase and beta-1,3-glucanase genes have exhibited enhanced tolerance to downy mildew incited by Plasmopara viticola. cDNA clones encoding chitinase and beta-1,3-glucanase have been isolated from a cDNA library, constructed from scab-infected Sumai-3 wheat, and introduced into a plant cloning vector to generate the plasmids pCAMBAR.chi.11 and pCAMBAR.638. Embryogenic cultures, established from in vitro-derived leaves, of Crimson Seedless were used as explants for Agrobacterium tumefaciens-mediated transformation studies. Sonication of somatic embryos in a bacterial suspension of A. tumefaciens and incorporation of anti-necrotic agents in the co-cultivation medium significantly enhanced transformation efficiency. Transformation efficiency of embryos with either chitinase or beta-1,3-glucanase gene was highest when embryos were suspended in a bacterial cell suspension at 0.5 OD600 and sonicated for 2 or 3 s at 60 kHz. Transformation efficiency with chitinase was highest on incorporation of 2 or 3 mg l(-1) phenylalanine, 1 or 2 mg l(-1) silver nitrate or 400 mg l(-1) l-cysteine in co-cultivation medium while incorporation of 20 mg l(-1) sodium thiosulphate produced highest transformation efficiency with beta-1,3-glucanase. Confirmed transgenic grapevine lines harboring anti-fungal genes exhibited higher levels of chitinase and beta-1,3-glucanase transcripts as well as enzymatic activities. Moreover, transgenic lines showed enhanced tolerance to P. viticola infection following detached leaf assays.
Keywords: Agrobacterium tumefaciens; Anti-oxidants; Downy mildew tolerance; Grapevine; Sonication